[PP.10.05] ALTERATIONS IN METALLOPROTEINASE 9 AND TISSUE INHIBITOR 1 LEVELS IN RESISTANT HYPERTENSION AND THEIR RELATIONSHIP TO LEFT VENTRICULAR HYPERTROPHY. (September 2016) - Barbaro, N.; Sabbatini, A.; Ritter, A.; Almeida, A.; Faria, A.; Brunelli, V.; Correa, N.; Modolo, R.; Pinho, C.; Fontana, V.; Moreno, H.
Abstract : Objective: Resistant hypertensive patients (RHTN) have unfavorable prognosis due to poor blood pressure (BP) control and higher prevalence of target organ damage. Deregulation of matrix metalloproteinases (MMPs) and their inhibitors are related to cardiac remodeling and left ventricular geometry in cardiac diseases.This study aimed to investigate the association between MMP-9 and TIMP-1 levels and the presence of LVH as well as compare its levels between resistant hypertensive patients (RHTN) and mild to moderate hypertensive (HTN). Design and method: This cross-sectional study was performed in the Outpatient Resistant Hypertension Clinic at the Hospital of the University of Campinas. Seventy nine patients classified as resistant hypertensive and 116 mild to moderate hypertensive patients (HTN) were included. Left ventricular mass index (LVMI) was calculated by dividing the LV mass by the body surface area. Plasma levels of MMP-9 and TIMP-1 were determined by ELISA. Results: Higher levels of TIMP-1 (median[IQR]) were found in RHTN RHTN (88.2 [77.4- 100.8]) ng/mL), compared with HTN individuals (79.7 [67.5- 99.6] p = 0.015), while lower levels of MMP-9 9 (23.9 [19.8 -54.2] vs. 38.1 [24.8 -64.0], p = 0.003) and consequently, decreased MMP-9/TIMP-1 ratio were observed in RHTN group (0.30 [0.20–0.56] vs. 0.53 [0.33- 0.85], p < 0.0001). Different patterns of correlation were observed of TIMP-1 with LVMI in the subgroups; in controlled hypertensive patients, a positive correlation was observed (r = 0.25, p = 0.003) whereas in RHTN, TIMP- 1 levels were inversely correlated with LVMI (r = -0.33 p = 0.02). Interestingly, multiple regression analysis showed that TIMP-1 levels are independent predictors for LVMI in RHTN but not in HTN subgroup. Conclusions: Our data suggest that MMP-9/TIMP-1 balance varies according to the severity of hypertension and are associated with resistant hypertension and left ventricular hypertrophy.